2015
DOI: 10.3855/jidc.6104
|View full text |Cite
|
Sign up to set email alerts
|

Are healthcare workers’ mobile phones a potential source of nosocomial infections? Review of the literature

Abstract: Mobile communication devices help accelerate in-hospital flow of medical information, information sharing and querying, and contribute to communications in the event of emergencies through their application and access to wireless media technology. Healthcare-associated infections remain a leading and high-cost problem of global health systems despite improvements in modern therapies. The objective of this article was to review different studies on the relationship between mobile phones (MPs) and bacterial cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 45 publications
(69 reference statements)
6
75
0
9
Order By: Relevance
“…by Selim et al showed the most common microorganisms on healthcare worker's cell phones were MRSA and Staphylococcus coagulase negative (13). Other similar studies also reported Pseudomonas species in addition to previous germs (12)(13)(14)(15). In 2012, Ustun et al reported that among 183 samples that were collected from cell phones of physicians, nurses and laboratory staffs, 179 (97.8%) were contaminated including Extended Spectrum Beta-Lactamases (ESBLs) producing E. coli (11.2%) and MRSA (9.5%) (16).…”
Section: Discussionmentioning
confidence: 73%
“…by Selim et al showed the most common microorganisms on healthcare worker's cell phones were MRSA and Staphylococcus coagulase negative (13). Other similar studies also reported Pseudomonas species in addition to previous germs (12)(13)(14)(15). In 2012, Ustun et al reported that among 183 samples that were collected from cell phones of physicians, nurses and laboratory staffs, 179 (97.8%) were contaminated including Extended Spectrum Beta-Lactamases (ESBLs) producing E. coli (11.2%) and MRSA (9.5%) (16).…”
Section: Discussionmentioning
confidence: 73%
“…En nuestro estudio encontramos que la mitad de los teléfonos presentaron contaminación. Cifras elevadas pero que no alcanzan las mostradas por otros autores como Ulger y cols (5) que alcanzaban hasta el 94,5% o Jayalakshmi y cols (16) con el 91,6%. Sin embargo, estudios como el de Smibert y cols (17) encontraron una contaminación del 7% de organismos multirresistentes implicando una baja evidencia, según estos autores, para el establecimiento de protocolos de limpieza para estos dispositivos en las UCI estudiadas.…”
Section: Discussionunclassified
“…una adecuada higiene, podría actuar como un reservorio para la transmisión de patógenos, encontrando datos muy variables en cuanto a los microorganismos detectados (4)(5)(6)(7)(8)(9) .…”
Section: Mensajes Claveunclassified
“…Ulger et al 6 em estudo recente abordou a questão do uso dos celulares dentro do hospital. Se por um lado, essa tecnologia facilita o fluxo de informação e a comunicação em eventos de emergência, por outro, seu uso pode estar relacionado a infecções hospitalares.…”
Section: Celular Ultrassonografia Raio-x Estetoscópiounclassified
“…O uso dos celulares pode, também, ser veículo de bactérias entre diferentes áreas do hospital, como sala de emergência, CTI e unidade de queimados. Em estudos prévios citados por Ulger 6 , a bactéria mais frequentemente relacionada foi Staphylococcus aureus, seguida de estafilococos coagulase negativos. Das bactérias gram negativas mais comuns, Acinetobacter spp.…”
Section: Celular Ultrassonografia Raio-x Estetoscópiounclassified